KAJIAN DESAIN TOILET TRANSPARAN TERHADAP PENGALAMAN PENGGUNA: A STUDY ON TRANSPARENT TOILET DESIGN AND USER PRIVACY EXPERIENCE - Kristel Karina Lestari; Sangayu Ketut Laksemi Nilotama; Ahadiat Joedawinata (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
Study on Transparent Toilet Design and User Privacy Experience Transparent toilets in Sudirman have become a captivating design transformation phenomenon in Jakarta. Privacy in the use of transparent toilets has become a crucial need. This study employs Maslow's hierarchy of needs to understand how user needs can be met through transparent toilet design. It aims to evaluate the extent of user privacy experiences with transparent toilets in Sudirman. The study applies privacy theory and visual comfort to assess the impact on user comfort. The design implications from this research emphasize the importance of comprehensively considering user privacy aspects in developing the interior design of transparent toilets. The findings reveal the complexity of challenges and privacy optimization in meeting user experience needs.